Prediksi Intensi Konsumen Melakukan Online Review Pada Layanan Online Food Delivery: Go-Food (Universitas Gresik, 2023)
Online reviews are important for the success of restaurants, especially restaurants that join online food delivery. This research is to find out why customers still do so few online reviews. Especially in online food delivery, how customers want to leave their reviews. This study relates to the usefulness of online food delivery applications and culinary products that are in online food delivery, as well as customer satisfaction when using online food delivery applications and intention to write online reviews. In addition, this study explores the moderating role of review involvement and helping the restaurant between customer satisfaction and their willingness to do online reviews. This study uncovers some interesting findings and adds to the literature in understanding online review post behavior. Theoretical and managerial implications will be explained in this study.